The horse encyclopedia - Hartley Edwards, Elwyn 1927-2007 (Dorling Kindersley Limited, 2016)
A stunning celebration of the equine world, The Horse Encyclopedia is a fully illustrated look at all the major horse and pony breeds and types, from the ponies of Dartmoor to the American mustang. Packed with gorgeous photographs of horse breeds from around the world, The Horse Encyclopedia is the definitive guide to the evolution, anatomy, and origins of each horse breed and its place in history, art, and culture. The Horse Encyclopedia also documents famous individual horses, as well as iconic owners, riders, and breeders, paying homage to equestrian history.